The Influence of Non Financial Compensation and Motivation on Employee Performance at PT Bank Rakyat Indonesia Unit Hasanuddin, Maros Branch - Nur Hilma; Jusri Jusri; Mulawarman Munsyir (Journal of Economics and Management Technologies, 2026)
The Objectives – This study aims to determine the Influence of Non-Financial Compensation and Motivation on Employee Performance at PT BRI Unit Hasanuddin, Maros Branch. The Methods/Approaches – This study employed a quantitative approach with a survey method. The survey method was used to collect data from respondents through a structured questionnaire. The population in this study included all employees of PT BRI Unit Hasanuddin, Maros Branch, with a total of 35 employees. Due to the relatively small population, this study used the Saturated Sampling Technique. The Results – The results of the t-test study indicate that the non-financial compensation variable does not significantly influence employee performance in this study, while the Motivation variable has a positive and significant influence on Employee Performance. And based on the results of the f-test, it shows that the Non-Financial Compensation and Motivation variables have a significant influence simultaneously on Employee Performance. The Research Implications – This research contributes to the practical understanding for PT BRI Unit Hasanuddin that providing good non-financial compensation (such as challenging work and a comfortable work environment) and strong motivation can significantly improve employee performance